1991
DOI: 10.1073/pnas.88.8.3353
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of PC3, a putatively secreted protein whose mRNA is induced by nerve growth factor and depolarization.

Abstract: PC3 is an immediate early gene induced by nerve growth factor in PC12 cells, a cell line derived from a tumor of the adrenal medulla that undergoes neuronal differentiation in the presence of nerve growth factor. This induction is independent of new protein synthesis as it can occur in the presence of cycloheximide. PC3 is also induced with similar kinetics, but at lower levels, by membrane depolarization (both in vivo and in vitro) and epidermal growth factor. It is induced at much lower levels by fibroblast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
1
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 44 publications
7
145
1
1
Order By: Relevance
“…Inspection of the deduced amino acid sequence of the ANA gene product (ANA) revealed its signi®cant homology at the amino-terminal half (residues 1 ± 115) to the corresponding portions of BTG1 (36% identical, Rouault et al, 1992), PC3 (38%, Bradbury et al, 1991), Tob (31%, Matsuda et al, 1996), and the Xenopus B9 protein (57%, Genbank) (Figure 1c and d). Therefore, we concluded that ANA is a member of Tob/BTG1 family antiproliferative proteins.…”
Section: Molecular Cloning and Characterization Of A Novel Tob Relatementioning
confidence: 99%
See 1 more Smart Citation
“…Inspection of the deduced amino acid sequence of the ANA gene product (ANA) revealed its signi®cant homology at the amino-terminal half (residues 1 ± 115) to the corresponding portions of BTG1 (36% identical, Rouault et al, 1992), PC3 (38%, Bradbury et al, 1991), Tob (31%, Matsuda et al, 1996), and the Xenopus B9 protein (57%, Genbank) (Figure 1c and d). Therefore, we concluded that ANA is a member of Tob/BTG1 family antiproliferative proteins.…”
Section: Molecular Cloning and Characterization Of A Novel Tob Relatementioning
confidence: 99%
“…The tob gene, together with the btg1 and pc3/tis21/ btg2 genes, forms a new antiproliferative gene family (Matsuda et al, 1996;Rouault et al, 1992Rouault et al, , 1996Bradbury et al, 1991;Fletcher et al, 1991). Both the BTG1 and Tob proteins suppress growth of NIH3T3 cells when overexpressed (Matsuda et al, 1996;Rouault et al, 1992).…”
mentioning
confidence: 99%
“…It is known that BTG2 is induced by NGF, FGF, IL-6, TPA, serum, EGF, and cAMP (Bradbury et al, 1991;Fletcher et al, 1991;Montagnoli et al, 1996) indicating that a number of stimuli triggering different transduction pathways can activate the transcription of this gene. Also Btg1 has been shown to be a direct target of different molecules, including T3 hormone (Rodier et al, 1999), Insuline-like Growth Factor 1 (IGF-1) (Vadgama et al, 2006), or FoxO3A (Bakker et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a structurally related gene has been characterized in amphioxus, the AmphiTOB gene (Holland et al, 1997). In vertebrates, the whole family is composed of at least six members that have been named differently in different species: Btg1, Btg2 (Tis21 in mouse and PC3 in rat), Btg3 (also named ANA for Abundant in Neuroepithelium Area), Btg4 (PC3B), Tob (Tob1), and Tob2 (Bradbury et al, 1991;Fletcher et al, 1991;Matsuda et al, 1996;Rouault et al, 1996;Guehenneux et al, 1997;Yoshida et al, 1998;Ikematsu et al, 1999). It has been proposed to name the family as APRO (AntiPROliferative) (Matsuda et al, 2001), but most studies and genetic databases continue using the BTG/Tob nomenclature, which will be adopted in this report.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation